EKSISTENSI DAN PERUBAHAN TRADISI MASSULO HENNE PADA MASYARAKAT PETANI DI DESA BULUTELLUE KABUPATEN SINJAI - Abdul Rahman (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2022)
This study aims to determine perceptions, values ​​and social changes in the implementation of the massulo henne tradition for the people of Tanete Rilau District. This study uses the method of observation, interviews and documentation. The results of the study show that the community considers land rites including massulo henne an obligation that must be fulfilled in accordance with the ancestral mandate. The noble cultural values ​​that are currently maintained by the community are closely related to the Sangia Seri teachings which include religious values, socio-cultural values, and economic values ​​and educational values. Changes that occur in the massulo henne tradition can be seen from the social and economic influence of a society.